Regeneration and Genetic Transformation Systems of Durum Wheat, Triticum durum - El-Arabi, Nagwa Ibrahim; Saleh, Jamal Rafik; Abdelhadi, Abdelhadi Abdallah; Abdallah, Naglaa Abdelmoneim (Journal of Biochemistry, Microbiology and Biotechnology, 2018)
Wheat is a major cereal crop for humans but quite recalcitrant in transformation. Establishment of regeneration system in wheat using immature embryos is not easy and time/cost-consuming. Herein, we developed a regeneration and transformation system using mature seeds in four pasta wheat cultivars. The MS medium with 2.0 mg/l 2,4-D and 2 mg/l BA was the optimum medium for developing shoots from calli. Wheat cultivars showed different regeneration frequencies response due to their genetic makeup. The cultivar Sohag-3 produced the highest regeneration frequency (93.2%) among the tested cultivars. Developed cultivars Sohag-3 and ACSAD1105 mature embryos were co-cultivated with Agrobacterium tumefaciens strain GV3101 with the binary vector pISV2678 harboring the bar gene and Î²-glucuronidase (gus) gene. The transformation efficiencies were 12.3 and 9.1% for cultivars Sohag-3 and ACSAD1105, respectively. The polymerase chain reaction (with specific primers for the transgenes) and the dot blot hybridization were used to confirm the integration of the transgene in transformed plants. The transformation percentages were reduced according to their expression and reached 5.6 and 4.6% for cultivars Sohag-3 and ACSAD1105, respectively. RT-PCR and northern blot analysis confirmed the expression of the gus gene only in the transgenic plants. The procedures developed in this study demonstrate the ability to produce transgenic wheat plants expressing the gus gene; hence, this protocol could be used to regenerate transgenic wheat plants expressing desirable and selective genes.